Dissociations between the horizontal and dorsoventral axes in body‐size perception. Issue 11 (20th March 2013) - Hashimoto, Teruo; Iriki, Atsushi
Abstract Body size can vary throughout a person's lifetime, inducing plasticity of the internal body representation. Changes in horizontal width accompany those in dorsal‐to‐ventral thickness. To examine differences in the perception of different body axes, neural correlates of own‐body‐size perception in the horizontal and dorsoventral directions were compared using functional magnetic resonance imaging. Original and distorted (−30, −10, +10 and +30%) images of the neck‐down region of their own body were presented to healthy female participants, who were then asked whether the images were of their own body or not based explicitly on body size. Participants perceived body images distorted by −10% as their own, whereas those distorted by +30% as belonging to others. Horizontal width images yielded slightly more subjective own‐body perceptions than dorsoventral thickness images did. Subjective perception of own‐body size was associated with bilateral inferior parietal activity. In contrast, other‐body judgments showed pre‐supplementary motor and superior parietal activity. Expansion in the dorsoventral direction was associated with the left fusiform gyrus and the right inferior parietal lobule, whereas horizontal expansions were associated with activity in the bilateral somatosensory area. These results suggest neural dissociations between the two body axes: dorsoventral images of thickness may require visual processing, whereas bodily sensations are involved in horizontal body‐size perception. Somatosensory rather than visual processes can be critical for the assessment of frontal own‐body appearance. Visual body thickness and somatosensory body width may be integrated to construct a whole‐body representation.